Approach to Neurometabolic Diseases from a Pediatric Neurological Point of View - KARIMZADEH, Parvaneh (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Karimzadeh P. Approach to Neurometabolic Diseases from a Pediatric Neurological Point of View. Iran J Child Neurol. 2015 Winter;9(1): 1-16. Abstract Objective Neurometabolic disorders are an important group of diseases that mostly are presented in newborns and infants. Neurological manifestations are the prominent signs and symptoms in this group of diseases. Seizures are a common sign and are often refractory to antiepileptic drugs in untreated neurometabolic patients. The onset of symptoms for neurometabolic disorders appears after an interval of normal or near normal growth and development.Additionally, affected children may fare well until a catabolic crisis occurs. Patients with neurometabolic disorders during metabolic decompensation have severe clinical presentation, which include poor feeding, vomiting, lethargy, seizures, and loss of consciousness. This symptom is often fatal but severe neurological insult and regression in neurodevelopmental milestones can result as a prominent sign in patients who survived. Acute symptoms should be immediately treated regardless of the cause. A number of patients with neurometabolic disorders respond favorably and, in some instances, dramatically respond to treatment. Early detection and early intervention is invaluable in some patients to prevent catabolism and normal or near normal neurodevelopmental milestones. This paper discusses neurometabolic disorders, approaches to this group of diseases (from the view of a pediatric neurologist), clinical and neurological manifestations, neuroimaging and electroencephalography findings, early detection, and early treatment. References Filiano JJ. Neurometabolic Disease in the Newborn. ClinPerinatol 33, 2006, 411-479. Van Karnebeek CDM, Stockler S. Treatable inborn errors of metabolism causing intellectual disability: A systematic literature review. Molecular Genetics and Metabolism, 105, 2012, 369-381. Abdel-Salam GMH, Abdel-Kader AA, Effat L, Gouda A, Hindawy A, El-Gammal MA. Clinical, Electroencephalographic (EEG), Neuroradiological and Molecular Correlations in Late-Detected Phenylketonuria (PKU) Patients.Egypt J. Neurol. Psychiat. Neurosurg., 2005, 42(2):391-406. Karimzadeh P, Ahmadabadi F, Jafari N, Shariatmadari F, Nemati H, Ahadi A, KarimiDardashti S, Mirzarahimi M, Dastborhan Z, ZareNoghabi J. Study on MRI Changes in Phenylketonuria in Patients Referred to Mofid Hospital/ Iran. Iran J Child Neurol. 2014 spring 8(2):53-56. Karimzadeh P, Jafari N, Ahmad Abadi F, Jabbedari S, Taghdiri MM, Alaee MR, Ghofrani M, Tonekaboni SH, NejadBiglari H. Propionic Acidemia: Diagnosis and Neuroimaging Findings of This Neurometabolic Disorder. Iran J Child Neurol. 2014 Winter; 8(1):58-61. Ozand PT, Rashed M, Gascon GG, Youssef NG, Harfi H, Rahbeeni Z, et al. Unusual presentations of propionic acidemia. Brain Dev 1994;16(Suppl):46-57 . Karimzadeh P, Jafari N, Jabbehdari S, Taghdiri MM, Nemati H, Saket S, Alaee MR, Ghofrani M, Tonakebni SH. Methylmalonicacidemia: Diagnosis and Neuroimaging Findings of This Neurometabolic Disorder (An Iranian Pediatric Case Series). Iran J Child Neurol. 2013 Summer; 7(3): 63-66. Radmanesh A, Zaman T, Ghanaati H, Molaei S, Robertson RL, ZamaniAA. Methylmalonicacidemia: brain-imaging findings in 52 children and a review of the literature. PediatrRadiol 2008 Oct;38(10):1054-6. Karimzadeh P, Ahmadabadi F, Jafari N, Jabbehdari S, Alaee MR, Ghofrani M, Taghdiri MM, Tonekaboni SH. Biotinidase Deficiency: A Reversible Neurometabolic Disorder (An Iranian Pediatric Case Series). Iran J Child Neurol. 2013 Autumn; 7(4):47- 52. Karimzadeh P, Pirzadeh Z, Ahmadabadi F, Jafari N, Jabbehdari S, Nemati H, Ghofrani M, Taghdiri MM, Tonekaboni SH, Mohammad-Reza Sharbatdaralaei. Glutaricaciduria type 1: diagnosis and neuroimaging findings of this neurometabolic disorder in an Iranian pediatric case series. International Journal of Developmental Disabilities 05/2014; DOI: 10.1179/2047387714Y.0000000039. Bernier FP, Boneh A, Dennett X, Chow CW, Cleary MA, Thorburn DR. Diagnostic criteria for respiratory chain disorders in adults and children. Neurology. 2002;59:1406–11. Wolf NI, Smeitink AM. Mitochondrial disorders: A proposal for consensus diagnostic criteria in infants and children. Neurology. 2002;59:1402–5. Majamaa K, Moilanen JS, Uimonen S, et al. Epidemiology of A3243G, the mutation for mitochondrial encephalomyopathy, lactic acidosis, and strokelike episodes: Prevalence of the mutation in an adult population. Am J Hum Genet. 1998;63:447–54. Lamont PJ, Surtees R, Woodward CE, Leonard JV, Wood NW, Harding AE. Clinical and laboratory findings in referrals for mitochondrial DNA analysis. Arch Dis Child, Arch Dis Child. 1998 Jul;79(1):22-7. Ferri R. Neurometabolic Disorders.Arch Neurol. 2005;62:1045-1046. PapettiL, ParisiP, LeuzziV, NardecchiaF, NicitaF, UrsittiF, Marra F, Paolino MC, Spalice A. Metabolic epilepsy: an update. Brain & Development. 2013 Oct;35(9):827-41. Salpietro V, Phadke R, Saggar A, Hargreaves IP, Yates R, Fokoloros C, Mankad K, Hertecant J, Ruggieri M, McCormick D, KinaliM. Zellweger syndrome and secondary mitochondrial myopathy. Eur J Pediatr. 2014 Oct 7 (Article in press). Schulz A, Kohlschütter A. NCL Disorders: Frequent Causes of Childhood Dementia. Iran J Child Neurol.2013 Winter; 7(1):1-8. Jalanko A, Braulke T. Neuronal ceroidlipofuscinoses. Biochim Biophys Acta 2009;1793:697-709. Karimzadeh P, Jafari N, NejadBiglari H, Jabbeh Dari S, Ahmad Abadi F, Alaee MR, Nemati H, SaketS, Tonekaboni SH, Taghdiri MM, Ghofrani M. GM2-Gangliosidosis (Sandhoff and Tay-Sachs disease): Diagnosis and Neuroimaging Findings(An Iranian Pediatric Case Series). Iran J Child Neurol. 2014 Summer;8(3): 55-60. Vanier MT, Duthel S, Rodriguez-Lafrasse C, et al. Genetic heterogeneity in Niemann-Pick C disease: a study using somatic cell hybridization and linkage analysis. Am J Hum Genet. 1996;58(1):118-125. Vanier MT. Niemann-Pick disease type C. Orphanet J Rare Dis. 2010;5:16. Meikle PJ, Hopwood JJ, Clague AE, et al. Prevalence of lysosomal storage disorders. JAMA. 1999; 281(3):249-254. Patterson MC, Hendriksz CJ, Walterfang M, et al. Recommendations for the diagnosis and management of Niemann-Pick disease type C: an update. Mol Genet Metab. 2012 ;106(3):330-3. Karimzadeh P, Tonekaboni SH, Ashrafi MR, Shafeghati Y, Rezayi A, Salehpour S, Ghofrani M, Taghdiri MM, Rahmanifar A, Zaman T, Aryani O, Shoar BN, Shiva F, Tavasoli A, and Houshmand M. Effects of Miglustat on Stabilization of Neurological Disorder in Niemann-Pick Disease Type C: Iranian Pediatric Case Series.J Child Neurol. 2013 Dec;28(12):1599-606. Gropman A. Imaging of Neurogenetic and Neurometabolic Disorders of childhood.Current Neurology and NeuroscienceReport. 2004. 4:139-146. Youssef-Turki IB, Kraoua I, Smirani S, Mariem K, Rhouma HB, Rouissi A, Gouider-Khouja N. Epilepsy Aspects and EEG Patterns in Neuro-Metabolic Diseases, Journal of Behavioral and Brain Science.2011. 1: 69-74. PapettiL, ParisiP, LeuzziV, Nardecchiac F, NicitaF, UrsittiF, MarraF, PaolinoMC,SpaliceA. Metabolic epilepsy: an update. Brain & Development. Article in press.Nov 2012.